A STUDY ON FUNDING AND FINANCIAL STRATEGY FOLLOWED BY WOMEN ENTREPRENEURS: A NEW WAY TO ENTREPRENEURIAL GROWTH OF BANGLADESH - Ara, Jesmin (Bangladesh Journal of Multidisciplinary Scientific Research, 2021)
Managing funds for venturing into a new business is a very challenging task for women. The goal of the study is to recognize congenial sources from where they can easily get funds to start their business and after starting a business which financial strategy they follow to expand their enterprise. To perform this task, primary data collection was carried out through a well-designed questionnaire and a total of 180 women entrepreneurs from different parts of the country took part in this program spontaneously. It is observed that usually women do not get bank loans easily, but they discovered that semiformal and informal sources of funds are available for their business and these loans help them to achieve the entrepreneurial goal. Although the interest rate is much higher, to be self-employed women must collect funds from these sources. 77 percent of women withdraw profit and their business follows the start small and stay small characteristics, but others save and re-invest their profit to expand the business operation. Despite the great loss caused by the Covid-19 pandemic, it is a light of hope that some women are doing very well by using the digital platform and providing home delivery services. From this paper, the new women entrepreneur can perceive what should be done and they will go through the right way. By following former entrepreneurs, they should take the right decision and bring success assuredly.